Utilization of Local Ingredients for the Production of High-Early-Strength Engineered Cementitious Composites - Hanwen Deng; Shunzhi Qian (Advances in Materials Science and Engineering)
The rapid repair and retrofitting of existing transportation infrastructure requires dimensional stability and ductile repair material that can obtain sufficiently high strength in a few hours to accommodate the large loading and deformation at an early age. Engineering cementitious composites (ECCs) is a class representative of the new generation of high-performance fiber-reinforced cement-based composites (HPFRCC) with medium fiber content. The unique properties of tremendous ductility and tight multiple crack behavior indicate that ECC can be used as an effective retrofit material. The wide application of this material in China will require the use of all local ingredients. In this study, based on Chinese domestic ingredients, including matrix materials and all fibers, high-early-strength ECC (HES-ECC) was designed under the guidance of strain-hardening criterion of ECC. The matrix properties and fiber/matrix interfacial micromechanics properties were obtained from three-point-bending test and single-fiber pullout test. The mechanical properties of HES-ECC were achieved by direct tensile test. The experimental results show that HES-ECC was successfully developed by using all Chinese materials. When using the domestic PVA fiber at 2%, the strength requirement can be achieved but only a low ductility. When using the domestic PE fiber at 0.8%, the strength and deformation requirement both can be obtained. The HES-ECC developed in this study exhibited compressive strength of more than 25 MPa within 6 hours, and an ultimate tensile strength of 5-6 MPa and tensile strain capacity of 3-4% after 60 days. Moreover, the cost of using domestic fiber can be largely reduced compared with using imported fiber, up to 70%; it is beneficial to the promotion of these high-early-strength ECCs in the Chinese market.